Glia and gliotransmitters on carbon nanotubes. (1st January 2017) - Min, Joo-Ok; Yoon, Bo-Eun
ABSTRACT: Introduction: Functionalised carbon nanotubes (CNTs) have been shown to be promising biomaterials in neural systems, such as CNT -based nerve scaffolds to drive nerve regeneration. CNTs have been shown to modulate neuronal growth and improve electrical conductivity of neurons. Methods: Cultured astrocytes on the functionalized CNTs (PEG, caroboxyl group) were assessed for distribution of GABA, glutamate uptake assay using isotope and change of conductance of CNTs by ATP. Immunostaining of GABA using anti-GABA (red), anti-GFAP (green) antibody in primary cortical astrocytes on MW-CNT and PDL coverslips. Results: The functionalization of CNTs has improved their solubility and biocompatibility and alters their cellular interaction pathways. Recently, CNTs have been shown to modulate morphofunctional characteristics of glia as well as neurons. Among the various types of glia, astrocytes express diverse receptors for corresponding neurotransmitters and release gliotransmitters, including glutamate, adenosine triphosphate, and γ-amino butyric acid. Gliotransmitters are primarily released from astrocytes and play important roles in glia–neuron crosstalk. Conclusion: This review focuses on the effects of CNTs on glial cells and discusses how functionalized CNTs can modulate morphology and gliotransmitters of glial cells. Based on exciting new findings, they look to be a promising material for use in brain disease therapy or neuroprosthetics.